Efektivitas Komunikasi Organisasi Subak Gede Sukawati di Kecamatan Sukawati, Kabupaten Gianyar - SUDARTA, I KOMANG ADI; SUARDI, I DEWA PUTU OKA; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
The Effectiveness of Subak Gede Sukawati Organizational Communication in Sukawati District, Gianyar Regency.  One of the subak that exist in Bali is located in Sukawati District, Gianyar Regency, namely Subak Gede Sukawati with 13 subak  tempekan  underneath. Subak Gede Sukawati is led by a  pekaseh gede , and each subak  tempekan  under it is led by a  pekaseh tempekan .  Pekaseh gede  communicates with  pekaseh tempekan  which is then passed on to  krama  subak. The purpose of this study was to find out how the process and effectiveness of Subak Gede Sukawati organizational communication. The selection of research locations was carried out purposively. The population in this study amounted to 1,138 people, with a total sample of 56 people, using purposive sampling and simple random sampling. The data analysis used is descriptive qualitative and quantitative. The results showed that Subak Gede Sukawati's communication process was classified as good to very good which was stated by 45% of respondents and 46% of respondents with an average score of 82.5. A good communication process is conveyed orally which exposes the sensory aspect of hearing. The effectiveness of Subak Gede Sukawati's organizational communication is classified as effective to very effective which is stated by 63% of respondents and 30% of respondents with an average score of 9.54. The effectiveness of communication is very dependent on the clarity of the message content and according to the context of the message.